Endopyhtic fungi as a bio control agent on anthracnose disease of rubber / Munirah Mahmud - Mahmud, Munirah (Faculty Of Plantation and Agrotechnology, 2018)
Antracnose disease caused by Colletotrichum species have cause a problem in rubber production in Malaysia. The pathogen could disrupt the yield production and also quality of the yield. It is one of the serious leaf diseases which affects the new flushes produced following the ‘wintering effect’, when the rubber tree loses its leaves during the dry season. The objective of the study were to determine the effectiveness of endophytic fungi to inhibit Colletotrichum species and to isolate and identify the morphology of Colletotrichum species based on morphological characteristic. In this study, endophytic fungi were used as a biological control agents and subtitution method instead of using chemical control that will give negative effect to human and environment. The endophytic fungi were isolated from healthy rubber leaves. These fungi can be useful for biological control of pathogens and plant growth promotion. Endophytic fungi do not have negative effect on the host plant it colonizing. Based on the result of the isolation, the endophytic species that have been successfully isolated is from Fusarium sp while the species for Colletotrichumis Colletotrichum gloeosporioides. Endophytic fungi were effective to inhibit mycelial growth of Colletotrichum species with 63.64% inhibition.The colonies of Colletotrichum is grey sparse. The conidia is masses and the conidia shape is cylindrical with round end while the colonies of endophytic fungi iswhite sparse and masses. The conidial shape is tablet shape or cylindrical shape with round ends.